The Study of Willingness to Pay for Bicycle Hire Services At Tourist Attractions in Thailand - D. Watthanaklang; V. Ratanavaraha; S. Jomnonkwao; T. Boonyoo; W. Nambulee (International Association of Lowland Technology, 2019)
Bicycles offer non-motorized transport that not only reduces energy consumption and pollution but also offers health benefits. However, most Thai people do not use bicycles. This study investigates the willingness to pay (WTP) for bicycle hire at tourist attractions in Thailand, which can inform strategies that encourage more Thai people to use bicycles. Data analysis considered socio-economic factors, such as gender, age, and level of education, average household income per month, type of tourist attraction, frequency of bicycle use, and type of bicycle. The analyses included the independent sample t-test and analysis of variance F-test. The samples for the analysis comprise 704 Thai tourists. From the results, it was found that WTP for bicycle hire between respondents’ gender for the age groups lower than 18 years and between 30–44 years was different. For type of bicycle, the differences were at statistical significance 0.05. The group having WTP for bicycle hire at a confidence level of 95% shared the same level of education, Average household income per month, frequency of bicycle use, and type of tourist attraction were not different. Government sectors or involved organizations can use this study to inform guidelines around suitable bicycle hire for target groups.